ChemInform Abstract: Blue Light: A Fascinating Journey (Nobel Lecture). Issue 33 (August 2015) - Akasaki, Isamu
Abstract Review: description of the historical progress that led to the invention of the first blue LED and related optical devices; 67 refs.